Austrosciara Schmitz & Mjöberg, 1924, a senior synonym of Ctenosciara Tuomikoski, 1960 (Diptera: Sciaridae) and the description of a new brachypterous species in the genus - Mohrig, Werner; Kauschke, Ellen; Heller, Kai (Zootaxa, 2017)
Three species of wing-reduced Sciaridae, obtained from pitfall trap material collected from Nothofagus forests in Victoria, Australia, were examined. The females, which were all very similar, do not belong to any of the wing-reduced sciarid genera known to us so far. They instead appear to be females of the genus Austrosciara Schmitz & Mjöberg, 1924, according to the original description and illustration, and one of the species appears to be conspecific with Austrosciara termitophila Schmitz & Mjöberg. The shape of the male hypopygium, as well as the tibial organ of this species in both sexes show typical features of species previously classified as Ctenosciara Tuomikoski, 1960. The genus Ctenosciara Tuomikoski, 1960 n. syn. has therefore to be considered a junior synonym of Austrosciara Schmitz & Mjöberg. A further species described as Austrosciara pedibusa sp. n., based on female specimens, is typically characterized by a deep sensory pit on the basal segment of the palpus. The female of a third species, listed as Austrosciara sp., is illustrated as well.